As the wheel turns toward the future of retailing. Issue 1 (2nd January 2021) - Babin, Barry J.; Feng, Cong; Borges, Adilson
ABSTRACT: What does the future hold for retailers? Certainly, many eras previous to the big-data and pandemic eras have come and gone and that same question could raise anxiety among those invested in retailing. Few metaphors in marketing have proved as enduring as the wheel of retailing. The contribution here is to discuss retail practice and research trends framed by the realization that, in some ways, nothing is new. Clearly, from a technology standpoint, we see changes in the tools of retailing at an ever-more rapid rate. But, the hub of the retail wheel is the customer and the value creation needed to promote retail success proves enduring. We conclude the discussion with an inventory of research items to keep academicians busy for the foreseeable future and by putting forth a definition of retailing that spans generations past and to come.